"Sacred noise" - Kovačič, Mojca (Muzikološki zbornik, 2016)
This paper considers the situation in which the anticipation of a new sound within public space gives rise to political, social, and ideological debates. It demonstrates how the religious sound of ezan (Muslim call to prayer) caused public discomfort even prior to becoming a part of Ljubljana%s soundscape, how the politics of power affected society and its religious sphere, and what kind of discourses take place in regard to the sounds associated with the Muslims in Slovenia.
Keywords: etnomuzikologija; ezan; Ljubljana; muslimani; razmerja moči; religijski zvok; zvonjenje